Direct Current Triboelectric Nanogenerators. Issue 45 (27th October 2020) - Song, Yiding; Wang, Nan; Wang, Yuanhao; Zhang, Renyun; Olin, Håkan; Yang, Ya
Abstract: The triboelectric nanogenerator (TENG) as a promising energy scavenging technology has been utilized to convert ambient mechanical energy into electric energy for meeting ever‐increasing energy consumption and the need for sustainable energy in modern life. However, the electric energy generated by the conventional TENG based on coupling the contact electrification and electrostatic induction is pulsed alternating current, which requires rectification measures to obtain the direct current (DC) power suitable for storing and driving electronic equipment, resulting in the limitation of its portability and energy utilization efficiency. Through the use of new materials and structures, novel direct current triboelectric nanogenerators (DC‐TENGs) with constant DC output characteristics provide an intelligent solution. Here, the development of DC‐TENG is reviewed, focusing on the working mechanisms of DC‐TENG based on various strategies. The important factors affecting the outputs and the main applications of DC‐TENGs are summarized. Moreover, the possible challenges and future direction for DC‐TENGs are also discussed. Abstract : The direct current triboelectric nanogenerator (DC‐TENG) is an emerging technology for directly converting mechanical energy into DC electric energy. The development of the DC‐TENG based on different strategies is summarized for the first time in terms of the progress in materials, structures, and working principles.